A randomized controlled trial of nasal airway ventilation technique in edentulous patients during anesthesia induction - Ling-Ling Wang; Xiao-Guang Guo; Yang Li; Fu-Shan Xue; Jian-Jun Yang (Scientific Reports)
Abstract Edentulous patients often experience difficult facemask ventilation during anesthesia induction, primarily due to inadequate facemask seal and air leakage. This randomized trial was designed to determine the efficacy and safety of an alternative ventilation strategy, namely the nasal airway ventilation technique, which involves the use of a nasal airway and a modified ventilation maneuver during anesthesia induction in edentulous patients. Eighty edentulous patients who underwent elective surgery with general anesthesia were randomly assigned to the nasal airway or facemask group. In the nasal airway group, a nasal airway was inserted and connected to the anesthesia ventilator, after which the mouth and nostrils were closed. In the facemask group, moistened gauzes were used to improve the facemask seal against hollow cheeks and the “VE-clamp” technique was applied for facemask ventilation. The primary outcome was the expired tidal volume during anesthesia induction. The expired tidal volume during anesthesia induction was significantly increased in the nasal airway group (median 5.6 mL/kg, interquartile range 5.0–5.9), compared with the facemask group (median 3.6 mL/kg, interquartile range 2.6–4.5), with a median difference of 1.9 mL/kg (95% confidence interval, 1.4 to 2.3; P < 0.001). A higher incidence of successful ventilation by a single anesthetist is observed in the nasal airway group than in the facemask group during anesthesia induction (100 vs. 82.5%; P = 0.018). There was no significant difference in the incidence of adverse events between groups. Our findings demonstrated that the nasal airway ventilation technique significantly and safely improved ventilation during anesthesia induction in edentulous patients. Thus, this technique can serve as a valuable alternative when facemask ventilation is inadequate in these patients.